2018
DOI: 10.1080/17457289.2018.1476359
|View full text |Cite
|
Sign up to set email alerts
|

Socialization and generational political trajectories: an age, period and cohort analysis of political participation in Britain

Abstract: The role of political socialization in explaining disengagement from specific modes of activism beyond voting remains largely unexplored, limited to date by available data and methods. While most previous studies have tended to propose explanations for disengagement linked to specific repertoires of political action, we propose a unified theory based on the different socialization experiences of subsequent generations. We test this theory using a new dataset of collated waves of the British Social Attitudes Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 75 publications
1
37
0
5
Order By: Relevance
“…Various methods have been proposed and used to deal with this problem in prior studies (e.g., Yang et al ; Luo ; Persson et al ) but arguably the most theoretically straightforward approach is to limit this collinearity by splitting respondents into broader categories of birth‐year cohorts, based on theory and prior research on historically distinctive formative periods. In this study, I base the categorization of cohorts on one which prior studies have found to be valid and theoretically meaningful when analysing political participation in Western Europe (Grasso ; Fox ; Grasso et al ). This categorization is based on the years in which respondents experienced a majority of their formative years and yields the following cohorts of citizens: Pre‐WWII generation: Born before 1926 Post‐WWII generation: Born between 1926–1945 60s and 70s generation: Born between 1946–1957 80s generation: Born between 1958–1968 90s generation: Born between 1969–1981 Millennial generation: Born after 1981 …”
Section: Methodsmentioning
confidence: 99%
“…Various methods have been proposed and used to deal with this problem in prior studies (e.g., Yang et al ; Luo ; Persson et al ) but arguably the most theoretically straightforward approach is to limit this collinearity by splitting respondents into broader categories of birth‐year cohorts, based on theory and prior research on historically distinctive formative periods. In this study, I base the categorization of cohorts on one which prior studies have found to be valid and theoretically meaningful when analysing political participation in Western Europe (Grasso ; Fox ; Grasso et al ). This categorization is based on the years in which respondents experienced a majority of their formative years and yields the following cohorts of citizens: Pre‐WWII generation: Born before 1926 Post‐WWII generation: Born between 1926–1945 60s and 70s generation: Born between 1946–1957 80s generation: Born between 1958–1968 90s generation: Born between 1969–1981 Millennial generation: Born after 1981 …”
Section: Methodsmentioning
confidence: 99%
“…Studies show that young people are less active in core representative institutions such as elections and political parties (e.g., Chou, 2017;Grasso et al, 2018). One interpretation of the developments in youth political engagement contends that young people do not want to be more active in democracy.…”
Section: Literature Review: Youth Political Participation and Implications For Democracymentioning
confidence: 99%
“…Consequently, young citizens' apparent lack of engagement in the traditional institutions of politics does not signal political apathy: on the contrary, young people are involved in political matters, but they participate in different ways than older generations do. Several studies investigating youth participation contends that the decline in electoral participation and party membership (e.g., Furlong and Cartmel, 2007;Bennett, 2008;Grasso et al, 2018), is evidence of a shift in young people's participation habits (e.g., Inglehart, 1997;Dalton, 2016;Chou, 2017;Pickard, 2019;Huttunen and Christensen, 2020). Instead of merely showing their opinions on the Election Day, young people participate in myriads of ways between elections, e.g., in single-issue movements, social movements, through ecological consumption and online activism, and they have a broader view of political participation than previous generations.…”
Section: Literature Review: Youth Political Participation and Implications For Democracymentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been a key development in European studies in which scholars use qualitative research to understand democratic linkages (Duchesne et al, 2013; Van Ingelgom, 2014)—which can help explain democratic linkages that have been documented using quantitative research (e.g. Hooghe & Stiers, 2016; Grasso, Farrall, Gray, Hay, & Jennings, 2019).…”
Section: Introductionmentioning
confidence: 99%